2005
DOI: 10.1074/jbc.m501332200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Complexes Formed between TSG-6 andInter-α-inhibitor That Act as Intermediates in the Covalent Transfer ofHeavy Chains ontoHyaluronan

Abstract: The high molecular mass glycosaminoglycan hyaluronan (HA) can become modified by the covalent attachment of heavy chains (HCs) derived from the serum protein inter-alpha-inhibitor (IalphaI), which is composed of three subunits (HC1, HC2 and bikunin) linked together via a chondroitin sulfate moiety. The formation of HC.HA is likely to play an important role in the stabilization of HA-rich extracellular matrices in the context of inflammatory disease (e.g. arthritis) and ovulation. Here, we have characterized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
294
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(317 citation statements)
references
References 52 publications
17
294
4
2
Order By: Relevance
“…HMW I␣I was also degraded by chondroitinase ABC, indicating that the HCs similarly had been rearranged. Moreover, inhibition of the TSG-6/HC2 transfer activity (14,28) prevented chondroitinase ABC from cleaving and releasing the two HCs, supporting that the authentic position was maintained (Fig. 3, lane 4).…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcmentioning
confidence: 67%
See 2 more Smart Citations
“…HMW I␣I was also degraded by chondroitinase ABC, indicating that the HCs similarly had been rearranged. Moreover, inhibition of the TSG-6/HC2 transfer activity (14,28) prevented chondroitinase ABC from cleaving and releasing the two HCs, supporting that the authentic position was maintained (Fig. 3, lane 4).…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcmentioning
confidence: 67%
“…1, lanes 1 and 3). Previously, it has been shown that the HC transfer reaction is HC2-and divalent cation-dependent (14,16,28). Therefore, samples without HC2 or without divalent cations were used as negative controls, and as expected, no HC transfer was observed in these samples (Fig.…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of ITIHs onto HA requires tumour necrosis factor a-induced protein 6 (TNFAIP6), also known as TNF-stimulated gene 6 (Jessen and Odum, 2003). TNFAIP6 forms a stable complex (Rugg et al, 2005) with ITIH and HA during the transesterification reaction (Sanggaard et al, 2005). This formation of ITIH-HA complexes is thought to play an important role in the stabilization of HA-rich extracellular matrices, with TNFAIP6 acting as an essential cofactor and catalyst (Rugg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…TNFAIP6 forms a stable complex (Rugg et al, 2005) with ITIH and HA during the transesterification reaction (Sanggaard et al, 2005). This formation of ITIH-HA complexes is thought to play an important role in the stabilization of HA-rich extracellular matrices, with TNFAIP6 acting as an essential cofactor and catalyst (Rugg et al, 2005). To date, five distinct ITIHs have been identified, encoded by five genes located on two different chromosomes (DiarraMehrpour et al, 1989;Himmelfarb et al, 2004).…”
Section: Introductionmentioning
confidence: 99%